Rákosi Mátyás, Gerő Ernő, Vas Zoltán és Farkas Mihály jelenlegi helyzete . Mátyás Rákosi's, Ermő Gerő's, Zoltán Vas', Mihály Farkas' Present Status - Héderváry, Claire de (1961)
Records of this digital collection were assembled to document the work of the UN Special Committee on the Problem of Hungary established on January 10, 1957 by the United Nations General Assembly for the purpose of investigating the 1956 Hungarian revolution. Principal contributor(s): Radio Free Europe Copy from the RFE Information Items Collection. Item No. 2307/61.